2020
DOI: 10.1016/j.invent.2020.100338
|View full text |Cite
|
Sign up to set email alerts
|

Treating perfectionism using internet-based cognitive behavior therapy: A study protocol for a randomized controlled trial comparing two types of treatment

Abstract: Perfectionism is characterized by setting high standards and striving for achievement, sometimes at the expense of social relationships and wellbeing. Despite sometimes being viewed as a positive feature by others, people with perfectionism tend to be overly concerned about their performance and how they are being perceived by people around them. This tends to create inflexible standards, cognitive biases, and performance-related behaviors that maintain a belief that self-worth is linked to accomplishments. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 42 publications
3
3
0
Order By: Relevance
“…The findings are consistent with Victor-Aigbodion et al [24] work, which reported a significant decrease in participants’ academic perfectionism following a CBC intervention. The current findings corroborate previous research demonstrating the efficacy of a cognitive behavioral model in addressing perfectionism issues [26,27] . Additionally, the findings corroborate those of Kothari et al, who reported a significant decrease in maladaptive perfectionism among their subjects [28] …”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The findings are consistent with Victor-Aigbodion et al [24] work, which reported a significant decrease in participants’ academic perfectionism following a CBC intervention. The current findings corroborate previous research demonstrating the efficacy of a cognitive behavioral model in addressing perfectionism issues [26,27] . Additionally, the findings corroborate those of Kothari et al, who reported a significant decrease in maladaptive perfectionism among their subjects [28] …”
Section: Discussionsupporting
confidence: 91%
“…The current findings corroborate previous research demonstrating the efficacy of a cognitive behavioral model in addressing perfectionism issues. [26,27] Additionally, the findings corroborate those of Kothari et al, who reported a significant decrease in maladaptive perfectionism among their subjects. [28] Additionally, the findings of this study corroborate those of Shafran et al, [29] who discovered that a cognitive behavioral treatment model was effective in reducing participants' maladaptive perfectionism in a randomized controlled trial.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Participants rated each life domain using a 10-point Likert-scale ranging from 0 = not at all to 10 = very much. The life domains were inspired by the type of value measures often used in Acceptance and Commitment Therapy ( Reilly et al, 2019 ), and are commonly employed in many clinical trials (e.g., Buhrman et al, 2020 ; Ehlers et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…Evidence has shown that internet-based interventions for common mental health issues often result in outcomes similar to those of face-to-face psychotherapy ( Carlbring et al, 2018 ). As for university students, recent studies have developed some guided iCBT programs that address their mental health concerns, such as perfectionism ( Buhrman et al, 2020 ), anxiety and/or depression (e.g. Harrer et al, 2021 ; Raevuori et al, 2021 ;), procrastination ( Küchler et al, 2019 ), and somatic symptom distress ( Hennemann et al, 2018 ); and some unguided iCBT programs addressing psychological or physical problems ( Fabritiis et al, 2022 ), social anxiety and insomnia ( Attridge et al, 2020 ), and public speaking fear ( Tillfors et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%